Analysis of Runway Pavement Overlay Design using FAARFIELD 2.1 - Kurnia Gilang Ramadani; Joewono Prasetijo; Aulia Sari, Yusra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
This study utilizes FAARFIELD software to calculate the necessary overlay thickness for the runway pavement at Hang Nadim International Airport. The evaluation relies on primary data, including field assessments such as Pavement Condition Index (PCI) analysis and Dynamic Cone Penetration (DCP) testing, to estimate subgrade bearing capacity. Secondary data is sourced from the Airport Pavement Management System (APMS), which provides historical pavement conditions, maintenance records, and aircraft traffic statistics. The results show that for the runway section from STA 0+000 to 4+025, with a subgrade CBR of 8%, the required overlay thickness is 55 mm (5.5 cm) of Hot Mix Asphalt (HMA). These findings incorporate projections of aircraft traffic growth over 20 years, ensuring the pavement's structural integrity despite increasing loads. The study also emphasizes the need for future research to refine methodologies for determining subgrade bearing capacity. While historical CBR data is available, updating field data will offer a more accurate reflection of current subgrade conditions. Moreover, DCP testing on the runway side may not accurately reflect conditions at the runway center, suggesting the use of core drilling to verify subgrade conditions at critical points. Core drilling can provide more precise depth measurements for reconstruction based on observed damage.